GENERATIONAL DIFFERENCES IN ORGANIZATIONS: challenges and possibilities of coexistence between different age groups in companies - De Souza, Ana Alice; Pinatti, Carla; Junior, Clóvis (Revista Interface Tecnológica, 2025)
This paper aims to present a behavioral analysis among the Baby Boomer, Generation X, Generation Y and Generation Z generations within the corporate environment and to understand how different generations act together. In order to ascertain the behavior of these generations, a qualitative survey was conducted involving 37 interviewees to understand how companies operate and what their perceptions are regarding the topic described. Dealing with these different views and expectations of the generations that operate requires companies to adopt a strategic and multifaceted approach. It is not just about managing conflicts between generations, but about promoting integration to maximize the potential of each group.